2023
DOI: 10.2147/jpr.s422050
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect and Potential Mechanisms of Acupuncture for Migraine Rats: A Systematic Review and Meta-Analysis

Abstract: To assess the inhibitory effect of acupuncture on pain symptoms in migraine models, and to further summarize the potential mechanisms of acupuncture in regulating hyperalgesia in the treatment of migraine. Materials and Methods: Literature search in databases such as China National Knowledge Infrastructure (CNKI), PubMed, and Web of Science (WOS) etc. The quality was evaluated by the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) bias risk assessment tool and Collaborative Approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“… 37 In addition, it has been observed that certain acupuncture points are particularly effective on hyperalgesia when compared with sham applications. 38 , 39 Moreover, some studies have reported local and widespread hyperalgesia in SIS. 40 , 41 Hyperalgesia is associated with higher pain perception in cases of shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In addition, it has been observed that certain acupuncture points are particularly effective on hyperalgesia when compared with sham applications. 38 , 39 Moreover, some studies have reported local and widespread hyperalgesia in SIS. 40 , 41 Hyperalgesia is associated with higher pain perception in cases of shoulder pain.…”
Section: Discussionmentioning
confidence: 99%